Legalitas Diskresi Pejabat Eksekutif dalam Praktik Birokrasi Pemerintahan: Kajian Komparatif Antara Indonesia dan Negara-Negara Eropa - Junaedi, Edy; Fitriyantica , Agnes (Postulat, 2025)
Discretion is an inherent authority granted to public officials to act on their own initiative when facing legal uncertainty or regulatory gaps, particularly in urgent or exceptional situations. In Indonesia’s bureaucratic governance, discretion often serves as a crucial tool in policy-making but remains vulnerable to abuse of power. The increasing criminalization of public policy decisions has sparked legal debates regarding the boundary between lawful administrative discretion. This doctrinal legal research aims to analyze the legality of executive discretion and the extent of official responsibility, especially in emergency contexts, through a comparative study with European countries adhering to the continental administrative law tradition. The selection of European countries, such as Germany and the Netherlands, is based on the maturity of their legal systems in formulating the principles of freies Ermessen, proportionality testing, and robust administrative oversight mechanisms over discretionary actions. The findings indicate that while Indonesia regulates discretion through the principles of freies Ermessen and general principles of good governance (AAUPB), the implementation still lacks strong accountability mechanisms. In contrast, European legal systems have established more precise standards and controls to prevent misuse. This study recommends a harmonization of Indonesia’s discretionary legal framework to align with the principles of a modern rule of law, including clearer boundaries of criminal liability for officials exercising discretion in extraordinary circumstances.